2005
DOI: 10.1055/s-2005-837470
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Interaction between Populus Esch5 and Piriformospora indica: A Transition from Mutualism to Antagonism

Abstract: Piriformospora indica (Sebacinaceae, Basidiomycota) is an axenically cultivable, plant growth promoting root endophyte with a wide host range, including Populus. Rooting of Populus Esch5 explants started within 6 days after transfer to WPM medium. If such plantlets with roots were inoculated with P. indica, there was an increase in root biomass, and the number of 2nd order roots was increased significantly. A totally different observation was recorded when the explants were placed into WPM with pre-grown P. in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 21 publications
0
31
0
1
Order By: Relevance
“…This close association of host cell death with massive fungal growth suggests that the fungus contributes to host cell death. Although P. indica can induce cell death in poplar under specific conditions on artificial medium (18), fungal culture filtrate did not show any phytotoxic activity on barley (data not shown). At particular interaction sites, we obtained cytological evidence that the fungus can attack and enwrap living (DAPI-positive) protoplasts (Fig.…”
Section: Balancing Of Host Cell Death and Impact Of The Cell Death Rementioning
confidence: 99%
“…This close association of host cell death with massive fungal growth suggests that the fungus contributes to host cell death. Although P. indica can induce cell death in poplar under specific conditions on artificial medium (18), fungal culture filtrate did not show any phytotoxic activity on barley (data not shown). At particular interaction sites, we obtained cytological evidence that the fungus can attack and enwrap living (DAPI-positive) protoplasts (Fig.…”
Section: Balancing Of Host Cell Death and Impact Of The Cell Death Rementioning
confidence: 99%
“…The order primarily contains the genera Sebacina, Tremelloscypha, Efibulobasidium, Craterocolla, and Piriformospora. Proteomics and genomics data about P. indica fungus have recently been described (Peškan-Berghöfer et al 2004;Shahollari et al 2005;Kaldorf et al 2005;Malla et al 2007a).…”
Section: Sebacinalesmentioning
confidence: 95%
“…It was suggested, therefore, that the fungus interferes with the host cell death program to form a mutualistic interaction with plants. Interaction with Populus Esch5 revealed that P. indica could be directed in its physiological behavior from mutualistic to antagonistic by specifically designed cultural conditions (Kaldorf et al 2005) hence making it a potential model system to study plant-microbe interactions. It provides a promising model organism for the investigation of beneficial plantmicrobe interactions, and enables the identification of compounds, which may improve plant growth, productivity and maintain soil productivity.…”
Section: Case Study: Priformospora Indica -A New Champion Of Symbiosismentioning
confidence: 99%